Contrast-enhanced sonography as a novel tool for assessment of vascular malformations - Oe, Yukiko; Orr, Lauren; Laifer-Narin, Sherelle; Hyodo, Eiichi; Koczo, Agnes; Homma, Shunichi; Kandel, Jessica; Meyers, Philip (Vascular Cell, 2010)
Abstract Background Vascular malformations with arteriovenous shunt components can cause significant disability, chronic pain, and functional impairment. Effective treatment may require serial procedures, yet an imaging modality optimized to control cost and reduce radiation exposure in this predominantly pediatric population has not yet been identified. Methods and Results We describe the use of contrast-enhanced sonography as a novel tool to define vascular anatomy and localize arteriovenous shunting in a young patient with a symptomatic vascular malformation. Conclusions This method may effectively reduce radiation exposure and cost, and additionally provide unique information about arteriovenous shunting, offering a novel imaging application for patients with these conditions.